Rice-Straw Mulch Reduces the Green Peach Aphid, Myzus persicae (Hemiptera: Aphididae) Populations on Kale, Brassica oleracea var. acephala (Brassicaceae) Plants - Silva-Filho, Reinildes; Silva Santos, Ricardo Henrique; Tavares, Wagner de Souza; Leite, Germano Leao Demolin; Wilcken, Carlos Frederico [UNESP]; Serrao, Jose Eduardo; Zanuncio, Jose Cola (Public Library Science, 2014)
Organic mulches, like peel and rice-straw, besides other materials affect the UV and temperature, which cause a reduction in the aphid arrival. The aim was to evaluate the effect of covering the soil with straw on the populations of the green peach aphid, Myzus persicae on the kale, Brassica oleracea var. acephala plants. The first experiment evaluated the direct effect of the rice-straw mulch and the second its indirect effect on aphid immigration, testing the plant characteristics that could lead to the landing preference of this insect. The third experiment evaluated the direct effect of the mulch on the aphid population. In the second and third experiments, four plants, each in a 14 L polyethylene pot with holes at the bottom, were used in areas with and without soil mulching. These pots were changed between areas, after seven days, to evaluate the effects of this change on the arrival of the winged aphids to the plants. Each plant was covered with anti-aphid gauze and inoculated with one winged M. persicae. Winged and apterous adults of this insect were counted per plant after 15 days. The temperature increased in the mulched plots to a maximum of 21-36(circle)C and to 18-32(circle)C in the plots with or without soil covering, respectively. Plant growth reduced the numbers of the winged aphids landing before and after they were moved to the bare soil plots. The nutrient content was similar in plants in both the mulched and no mulched plots. The population growth of M. persicae was higher in the control than in the mulched plots. This was partially due to temperatures close to 30(circle)C in these plots and changes in the plant physiology. The soil mulching with rice-straw decreased the M. persicae landing, increased the plot temperatures and improved the vegetative growth of the kale plants.